Shifting Career Landscapes: Analyzing the Fall in Physician-Owned Practices - Aabedi, Andre; Wang, Vera; Sahafi, Ramtin; Agrawal, Devendra K (Archives of Clinical and Medical Case Reports, 2026)
Over the past several decades, the structure of physician employment in the United States has shifted markedly, with a growing proportion of physicians choosing employed positions over private practice. This transition reflects broader economic, regulatory, and organizational changes within the healthcare system. This literature review examines the decline in physicians entering private practice and analyzes the economic, administrative, professional, and market-driven factors contributing to this trend, as well as its implications for physician autonomy, patient care, and healthcare costs. A comprehensive review of national workforce data, longitudinal studies, and peer-reviewed literature published between 1983 and 2024 was conducted. Trends in physician employment were evaluated across specialties, geographic regions, and demographic groups, with particular attention to policy changes, healthcare consolidation, and evolving practice models. The proportion of self-employed physicians declined from 35.2% in the early 2000s to under 25% by the mid-2010s, with continued declines in subsequent years. Contributing factors include rising overhead costs, declining reimbursement, increasing regulatory and administrative burdens, and narrowing income differentials between employed and self-employed physicians. Younger physicians and women demonstrate a stronger preference for employment, often citing worklife balance, financial stability, and organizational support. Healthcare consolidation, hospital employment, and private equity acquisition further limit opportunities for independent practice. The ongoing decline of private practice has significant implications for physician autonomy, continuity of care, healthcare spending, and patient-physician relationships. While employed models offer stability and infrastructure, they may compromise professional independence and increase system-level costs without improving care quality. Alternative models such as direct primary care and concierge medicine may offer partial solutions but raise concerns regarding equity and access. Structural reforms in reimbursement, regulation, and practice support are necessary to preserve a diverse and sustainable physician workforce.